Cultivation of oil flax at direct sowing in the conditions of the North Kazakhstan - S. A. Tulkubaeva; V. G. Vasin (Новые технологии, 2017)
The studies have revealed that flax oilseed sown on herbicide fallow ripened faster compared to options on wheat stubble, for an average 4-6 days. Crops on wheat stubble were inferior to those of herbicide fallow by 3-7% in terms of the overall survival of plants. The highest yield of flax oilseed was shown in the herbicide fallow with a row spacing of 23 cm. The application of desiccation 10 days prior to harvesting increased the yield of this crop by 5-7%.